Developing a big book has a conservation character in early reading - Nugraheti Sismulyasih Sabilillah; Otang Kurniaman (Jurnal Prima Edukasia, 2019)
A teacher must be able to develop learning media that are able to facilitate the transfer of knowledge they have, for the purpose of this study is how to develop the big book media with conservation characteristics in early reading. The results of the development of this media are carried out using the Research and Development (R D) research method, with the experimental subject covering three parts, namely needs analysis, media development stage, and media effectiveness test. Research instruments using questionnaires (open and closed questions), interviews, observation, documentation. The results of this study show in media validation with a total score of 80 with very good categories, deficiencies in media development are revised according to the notes from experts. Judging from the results of the validation about the content of the material in the big book conservation characteristics were obtained at 93% with very feasible criteria to be used by students and can be tested to see the effectiveness of big book media with conservation characteristics with many students 19 people in one class held at SD Labschool Unnes. Therefore the development of big book media with conservation characteristics is very effective in learning early reading.